2015
DOI: 10.1002/jmri.24871
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast‐enhanced MRI evaluates the early response of human head and neck tumor xenografts following anti‐EMMPRIN therapy with cisplatin or irradiation

Abstract: Purpose To assess the early therapeutic effects of anti-EMMPRIN antibody with/without cisplatin or X-ray radiation in head and neck cancer mouse models using dynamic contrast enhanced magnetic resonance imaging (DCE-MRI). Materials and Methods Mice bearing SCC1 (or OSC19) tumor xenografts were treated with anti-EMMPRIN antibody, radiation, cisplatin, or anti-EMMPRIN antibody plus cisplatin (or radiation) for a week (n=4–5 per group). DCE-MRI was carried out on a 9.4T small animal MR scanner on days 0, 3, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…There is less reported research related to intra-treatment monitoring using DCE-MRI compared to DWI possibly because DCE-MRI requires an intravenous injection of a contrast agent. There is some early work in tumour xenografts to suggest a rise in tumour K trans may occur over the first few days of treatment [ 35 ], and in human subjects to suggest a rise in plasma flow at two weeks [ 36 ]. It is postulated that an early rise in K trans is due to damage to the blood vessels causing them to temporarily become leakier, which potentially could increase the delivery of chemotherapeutic agents into the tumour.…”
Section: Main Textmentioning
confidence: 99%
“…There is less reported research related to intra-treatment monitoring using DCE-MRI compared to DWI possibly because DCE-MRI requires an intravenous injection of a contrast agent. There is some early work in tumour xenografts to suggest a rise in tumour K trans may occur over the first few days of treatment [ 35 ], and in human subjects to suggest a rise in plasma flow at two weeks [ 36 ]. It is postulated that an early rise in K trans is due to damage to the blood vessels causing them to temporarily become leakier, which potentially could increase the delivery of chemotherapeutic agents into the tumour.…”
Section: Main Textmentioning
confidence: 99%
“…Dynamic contrast-enhanced MRI (DCE-MRI) can assess the flow of blood through vessels in scanned tissues and therefore enables non-invasive characterization of tumour vascularity and perfusion 12. Due to lack of standardization of data acquisition and analysis12, the results of studies assessing the value of DCE-MRI derived parameters are still scarce and contradictory 13, 14, 15. In addition, studies addressing prognostic values of DCE-MRI parameters acquired early during treatment are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they could reduce the number of local metastases and improve survival with the addition of CD147 antibodies to the radiation treatment. Similarly, Kim et al determined that combining anti-CD147 antibody administration with radiation treatment had a synergistic effect in reducing tumor volume in a head and neck tumor mouse model [46]. Using a small molecule inhibitor, Fu et al showed in vivo that CD147 inhibition decreased progression in a model of metastatic hepatocellular carcinoma [47].…”
Section: Discussionmentioning
confidence: 99%